PEMBERDAYAAN PENYANDANG DISABILITAS OLEH DINAS SOSIAL KOTA KEDIRI - Krisnada Krisnada; Sugeng Widodo (Universitas Kadiri, 2019)
Abstract People with disabilities have physical and mental disabilities that have differences when compared to normal people, therefore there needs to be special attention from the government to empower or positive activities that are useful to hone the skills of the people with stability. Therefore, the role of the government is necessary for the development of people with disabilities. Through social services empowerment of people with disabilities is more targeted and focused. The purpose of this research is to decrypt what efforts are made as well as what obstacles are faced in the empowerment of people with disabilities. The type of method used in this study is a descriptive method with a qualitative approach. Data collection techniques used are, observation, interview, documentation. The result of this research is that the efforts made by Social Services are social assistance for severe disabilities in the form of money, as well as training but stalled per the year 2018 because it is focused in Dipnaker. Besides, there is assistance from the ministry in the form of non-cash social assistance for all classifications of people with disabilities. There are also other supporting activities as well as UPSK from the Social Service of East Java Province. Keywords: empowerment; disability; government role Abstrak Para penyandang disabilitas memiliki kelemahan secara fisik dan mental yang memiliki perbedaan bila dibandingkan dengan orang-orang normal, oleh sebab itu perlu adanya perhatian khusus dari pemerintah untuk memberdayakan ataupun kegiatan yang bersifat positif yang berguna untuk mengasah kemampuan para penyandang stabilitas. Maka dari itu peran pemerintah sangatlah perlu dalam pembinaan penyandang disabilitas. Lewat Dinas Sosial pemberdayaan penyandang disabilitas lebih terarah dan fokus. Tujuan penelitian ini untuk mendekripsikan upaya apa yang dilakukan serta kendala apa yang dihadapi dalam pemberdayaan penyandang disabilitas. Jenis metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan yaitu, observasi, wawancara, dokumentasi. Hasil dari penelitian ini adalah upaya yang dilakukan Dinas Sosial adalah bantuan sosial untuk disabilitas berat berupa uang, dan juga pelatihan namun terhenti pertahun 2018 karena difokuskan di Dipnaker. Selain itu terdapat bantuan dari kemensos berupa bantuan sosial non tunai untuk semua klasifikasi penyandang disabilitas. Terdapat juga kegiatan penunjang lain dan juga UPSK dari Dinas Sosial Provinsi Jawa Timur.Kata Kunci: pemberdayaan; penyandang disabilitas; peran pemerintah